Pemberdayaan Perempuan melalui Pelatihan Pengolahan Olos menjadi Frozen Food sebagai Upaya Peningkatan Keadilan Gender: Sebuah Research - Cesta Izzati Ukarana; Azzahra Elvina Sari; Srinandya Harum Caryarini; Vistaufa Wardhatul Chomairha; Raka Ahmad Rievai; Muhammad Rizaluddin Masdiningrat; Nanda Gusfiani Cahyo; Nurul Hidayati (Universitas Pahlawan Tuanku Tambusai, 2026)
This article aims to empower the community based on gender equality through seminars and training on processing olos into frozen food products. The method employed is a Participatory Action Research (PAR) approach, which involves active community participation from the planning stage through to activity evaluation. The research results demonstrate that the training successfully enhanced participants' skills in producing clean, innovative, and high-value olos frozen food, while also increasing community awareness of the importance of equal roles between men and women in families and society. The implications of this initiative include the emergence of new business opportunities based on local food products, supporting household economic independence and fostering fairer, more harmonious social relationships. However, the program's success requires sustained support and broader participation to amplify its impact at the community level. This program also plays a crucial role in raising societal awareness of gender justice, which is expected to be widely internalized within the community.